Analysis of milkfish meatballs with the addition of legume protein isolate - Siti Munawaroh; Bayu Kanetro; Agus Slamet (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
A popular and nutrient-rich fish jelly product called milkfish meatballs also includes saturated fatty acids and amino acids that are linked to an increased risk of cardiovascular disease. The goal of this study was to create milkfish meatballs with the best and desired chemical, physical, amino acid, fatty acid, and cholesterol profiles by adding legume protein isolate. The study's nine treatments included milkfish meatballs with soy protein isolate, sword kara protein isolate, and cowpea protein isolate added in amounts of 0%, 15%, and 30%, respectively. The produced meatballs underwent physical (texture, folding test, color test), chemical (proximate), and preference analysis. After analyzing the fatty acid profile, amino acid profile, and cholesterol before and after in vitro digestion, the two most popular treatments (milk meatballs with the addition of sword kara protein isolate/cowpea protein isolate or milkfish meatballs with the inclusion of sword kara protein isolate) were chosen. The milkfish meatballs that received the best treatment were those with the addition of 15% soy protein isolate and 30% swordfish protein isolate, with ratios of omega-6 to omega-3 of 2.176 and 1.811, respectively, and ratios of arginine to lysine of 1.49 and 0.99, respectively. This study's findings suggest, milkfish meatballs with the addition of 30% karapel protein isolate have the best preference value and the ability to serve as a functional diet to prevent hypercholesterolemia